The Rule of Law for the Right to Inclusive Education in Indonesia - Maya Indrasti; Faridah Jalil (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
Indonesia is committed to guarantee the right to education for all citizens without exception. The commitment of Indonesia to Education for All (EFA) leads to the fulfillment of inclusive education policies. The people of Indonesia tend to understand inclusive education as education for people with disabilities. On the other hand, inclusive education has a broader meaning, which does not refer only to special education. Furthermore, it also covers education with special services. The essence of inclusive education is to remove barriers that limit all marginalized learners, to respect diversity and needs, to create patterns of education without discrimination, and ultimately to achieve quality education. People’s understanding leads to questions about inclusive education in legal context, as well as the rules of inclusive education in Indonesia. This paper contains a qualitative study with a historical-doctrinal approach. The study aims to explain the right to inclusive education listed in the rules and regulations in Indonesia and their problems. From the normative point of view, the rules on inclusive education are regulated in the Law Number 8 of 2016 on Persons with Disabilities and the Regulation of the Minister of National Education Number 70 of 2009. Furthermore, the rules of inclusive education can also be found in several other regulations implicitly. Most of the rules have stipulated provisions that include the right to education. Therefore, the Government appears to be progressively realizing the respect, protection, and fulfillment of the right to education, including inclusive education, for all people of Indonesia.Aturan Hukum Hak atas Pendidikan Inklusif di Indonesia AbstrakIndonesia berkomitmen menjamin hak atas pendidikan bagi seluruh warganya tanpa terkecuali. Komitmen Indonesia terhadap Pendidikan untuk Semua atau Education for All (EFA) membawa pada komitmen dalam pemenuhan kebijakan pendidikan inklusif. Masyarakat Indonesia memiliki kecenderungan memahami pendidikan inklusif sebatas pada pendidikan bagi penyandang disabilitas. Di lain sisi, pendidikan inklusif memiliki makna luas tidak saja dalam konteks pendidikan khusus namun juga pendidikan layanan khusus Inti dari pendidikan inklusif adalah untuk menghilangkan hambatan yang membatasi semua peserta didik termarginalkan, menghormati keberagaman dan kebutuhan, sehingga dapat menciptakan pola pendidikan jauh dari diskriminasi, dan pada akhirnya dapat mencapai pendidikan yang berkualitas. Kecenderungan pemahaman masyarakat tersebut membawa pada pertanyaan mengenai pemahaman pendidikan inklusif dalam konteks hukum dan bagaimana aturan pendidikan inklusif di Indonesia. Tulisan ini adalah kualitatif dengan pendekatan doktrinal historis. Tulisan ini bermaksud menjelaskan hak atas pendidikan inklusif yang tercantum dalam aturan-aturan hukum di Indonesia serta permasalahannya. Dari segi normatif, aturan tentang pendidikan inklusif diatur dalam Undang-undang nomor 8 tahun 2016 tentang Penyandang Disabilitas dan Peraturan Menteri Pendidikan Nasional nomor 70 tahun 2009. Namun, secara implisit aturan terkait pendidikan inklusif dalam konteks pendidikan layanan khusus juga dapat ditemukan di beberapa peraturan lain. Aturan-aturan tersebut sebagian besar telah mengatur ketentuan-ketentuan yang dapat mengimplementasikan indikator-indikator hak atas pendidikan. Dengan demikian, Pemerintah nampak secara progresif memenuhi penghormatan, perlindungan dan pemenuhan hak atas pendidikan pendidikan inklusif bagi semua. Kata Kunci: Hak Atas Pendidikan, Pendidikan Inklusif, Pendidikan untuk Semua (EFA)DOI: https://doi.org/10.22304/pjih.v6n3.a9